Cultural invasion continued: The ongoing colonisation of Tikanga Maori - Mikaere, Ani (Yearbook of New Zealand Jurisprudence, 2005)

Māori Self-Determination: In the Modern Political Context - O'Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2005)
Keywords: Commonwealth; Democracy; Political Parties; Te Tiriti o Waitangi

The concept of partnership and The Treaty of Waitangi: three case studies - Morrison, Sandy (He Puna Korero: Journal of Maori & Pacific Development, 2005)
Keywords: co-governance; partnership; tiriti o waitangi/treaty of waitangi; treaty principles

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Developments in Indigenous Peoples' Rights under International Law and their Domestic Implications - Charters, Claire (New Zealand Universities Law Review, 2005)

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism

Ethnic Diversity in a Global Economy: A Case - Study of Māori Self Determination - Margaritis, Dimitris; Sullivan, Ann (The International Journal of the Humanities: Annual Review, 2005)
Keywords: sovereignty; tino rangatiratanga